Non-litigasi sebagai Mekanisme Penyelesaian Sengketa Lingkungan Bagi Perusahaan di Indonesia - Abduh, Muhammad (Jurnal Hukum Statuta, 2024)
Environmental problems have occurred in the global scope, both developed and developing countries. Environmental problems are not only problems of developed countries or industrialized countries including Indonesia. Efforts to overcome environmental problems in developing countries have no other choice but to carry out development. Without the level of development, people will decline, and the environment will be increasingly damaged. Development must still be carried out without damaging the environment. This balance must be maintained in order to preserve the environment. Indonesia has been paying attention to environmental management since 1972. Settlement of environmental disputes through litigation does not produce many results. Dispute resolution through non-litigation channels assumes that dispute resolution through litigation results in very disappointing results. This study wants to conduct a study related to the implementation of Government Regulation No. 54 of 2000 concerning Service Providers for Environmental Dispute Resolution Services Outside the Court and find obstacles and solutions in resolving environmental disputes out of court. The implementation of Government Regulation No. 54 of 2000 at the central government level has established a service provider institution based on the Decree of the State Minister of the Environment Number 77 of 2003 concerning the Establishment of an Out-of-court Environmental Dispute Resolution Service Provider (LPJP2SLH) at the Ministry of the Environment, but its performance has not yet been felt. Keywords: Non Litigation; Dispute Settlement; Environment